PELATIHAN MEMUKUL DENGAN BEBAN MENINGKATKAN KEKUATAN DAN KECEPATAN PUKULAN LURUS KIRI DAN KANAN DARI PADA PELATIHAN MENDORONG KATROL DENGAN BEBAN - Loda, Imakulata Magi; Adiatmika, I Putu Gede; Fufu, Oktovianus; Jawi, I Made; Satriyasa, Bagus Komang; Griadhi, I Putu Adiartha (Sport and Fitness Journal, 2017)
Background: Straight punch or jab punch is one punch in boxing. Jab is a blow provocation done by hand in the front position to distract the opponent. Not infrequently blow jab could be ejected violently. Strength and speed jab is in need to knock out the opponent. Therefore we need the right training. Objective: Training hit by the load and drive pulley with weights aims to increase the strength and speed of the jab and stright punch blow. Method: Experimental research has been done with the design Randomized Pre-Post Test Control Group Design on Student SKO Flobamora Kupang. Total sample of 18 people, divided into two groups and each group of nine people. Group 1 was given training with weights and hit the second group training encourages pulley with weights. Research for six weeks with a frequency of exercise three times a week. speed is measured with a stopwatch, Strength was measured with a hand dynamometer before and after treatment, and the differences were statistically tested. Result: T independent test shows the speed and the strength among the groups before the training did not differ (24.44? 0.882 /5 seconds and power punches 36.44 ? 1,878 kg After training the average speed punch 24.44?0.882 blow before training 21,00± 1,118 blows / 5 seconds and average power punches 33.11 ? 1.900 blows / 5 seconds and average power punches 38.22 ± 1.202 kg. In Group 2 average speed of 33.56?1.590 kg. Average speed punch after training were 29.11 ? 1,364 blows / 5 seconds and average power punches ?Results of paired t-test showed the average speed of a punch in Group 1 before training 21.33±1,118 (p > 0.05) and after training was significantly different (p <0.05) test shows Training hit with loads more increase the strength and speed of the push pulley with weights. Conclusion: Training concluded hit with a load greatly increase the speed and strength of the left and right straight punches instead of pushing a pulley with weights together to give the effect of increased power and speed and a left straight punchright (p <0.05). An increase in one group is better than the training push pulley with weights on the strength and speed of the left and right straight punches. Suggestion: It is advisable to use a hitting training with weights in the training process in the recruitment of athletes, because it gives a better effect.